A life extrapolation model using accelerated equivalent luminance and its application. Issue Volume 35:Issues 2(2023) (3rd April 2023) - Zhang, Jianping; Zhang, Yinjie; Sun, Lei; Fu, Jian; Zhou, Qing; Hu, Jun; Bao, Cheng; Chen, Siyi
Abstract: Aiming at predicting the life of vacuum fluorescent display (VFD) accurately, four groups of constant-stress accelerated degradation tests (ADTs) were conducted, and the life extrapolation model of accelerated equivalent luminance (LEMAEL) based on each test sample was proposed. In this model, firstly, Weibull function was employed to fit luminance degradation data of each sample at each stress. Secondly, Logistic function was determined by Anderson-Darling test to respectively describe the distributions of shape and scale parameters, and the degradation formula of accelerated equivalent luminance was obtained to estimate accelerated life. Finally, Power function was selected by comparing determination coefficients to fit the data points formed by accelerated life and stress, and thereby VFD life was extrapolated. The results indicate that the collected test data of each sample objectively reflect VFD luminance characteristics; the degradation formula intuitively exhibits the luminance variation law at each accelerated stress, and Power function accurately reveals the relationship between life and stress; LEMAEL is characterized by high precision and large amount of data information, which not only actualizes the accurate life estimation for light-emitting devices without conventional life tests, but also provides entirely new modeling ideas and thoughts for reliability evaluation and life prediction of products.